Can shoulder muscle coordination during the support scale at ring height be replicated during training exercises in gymnastics? - Bernasconi, S. M.; Tordi, N. R.; Parratte, B. M.; Rouillon, J. D. R. (The Journal of Strength and Conditioning Research, 2009)
The support scale at ring height, the swallow, is a difficult strength element, usually performed in gymnastics. Coaches try to simulate the swallow position during training to strengthen muscles, specifically in the position used for competition. However, the real effect of this position's simulation on muscle force and coordination and consequently on the muscle activity has not been determined. The purpose of the study was to compare muscle activity and coordination during a swallow performed on the rings, using a counterweight and during 2 training exercises using dumbbells or barbells, respectively. Six top-level gymnasts participated in the study. Electromyograms from the biceps brachii, triceps brachii, deltoideus (clavicular part), pectoralis major, serratus anterior, infraspinatus, trapezius (middle part), and latissimus dorsi in the right shoulder were collected during the 4 exercises and analyzed using root mean square (RMS) and mean power frequency (MPF). The RMS were normalized to the maximal voluntary contraction, and a co-activation index was also determined between biceps and triceps brachii. Our results show specific shoulder muscle coordination for each exercise. As compared with the swallow on the rings, the pectoralis major participates less in shoulder flexion during the counterweight exercise, whereas the deltoideus is more activated during the dumbbells exercise (p < 0.05). The barbell exercise reduces the participation of the serratus anterior in stabilizing the scapula (p < 0.05). Training exercises must therefore be chosen with knowledge of the specific muscle coordination induced by each. The counterweight exercise preserves the pectoralis major. The barbell exercise reduces participation of the serratus anterior. The dumbbells exercise may be useful to prepare the rotator cuff muscles carefully for use.